Philosophical Meaning of Traditional Wedding Rituals of the Singkil Tribe: Makna Filosofis Pada Ritual Adat Pernikahan Suku Singkil - Rizki, Annisa; Aslam Nur, Aslam Nur; Munawiah (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2024)
This article aims to describe the philosophical meaning of the traditional weddings of the Singkil Tribe based on data from Lae Butar Village, Gunung Meriah District, Aceh Singkil Regency. This research uses descriptive methods with data collection techniques, namely observation, interviews, and documentation. In the process of presenting data, researchers use data analysis techniques that describe, interpret and validate. The results of the research show that wedding customs are still implemented and maintained by the people in Lae Butar Village to this day. Meanwhile, the traditional wedding procession of the Singkil Tribe in Lae Butar Village is, first, mekhisik, tandek sintua, mebagah, khapat famili, umba-umba and gaba-gaba. The second day, namely, marriage contract, mangan mido tawar, slaughtering animals, religious lectures, hine tetuhu. The third day involve dalalel khairat, tepung tawakh, and hine menangko. On the last day is mangan mekhadat, temetok and pengakhak Mangan mido tawar has a philosophical meaning, which means that those holding a wedding will receive blessings and avoid undesirable things. Tepung tawar means, so that the bride and groom get blessings from the procession. The Singkil Tribe wedding procession in Lae Butar Village combines marriage and custom directly on the same day.